EXPLORATION OF PROBLEM-BASED LEARNING MODELS IN URBAN EDUCATION CONTEXTS: IMPLICATIONS FOR LEARNING INDEPENDENCE - Abd. Muis; Siti Fatmah Hiola (International Journal of Teaching and Learning, 2025)
This research aims to explore the relevance and effectiveness of the Problem-Based Learning (PBL) model in the context of urban education, as well as its implications for strengthening students' learning independence. The study was conducted using the library research method by analyzing various scientific sources such as national and international journals, reference books, research reports, and relevant dissertations. The results of the thematic synthesis show that PBM is capable of responding to the complexities of urban classrooms through contextual, collaborative, and problem-oriented learning approaches. PBM has been proven to enhance indicators of learning independence, such as self-regulation ability, decision-making, and learning initiative. However, the implementation of this model in urban environments faces challenges such as time constraints, teacher administrative burdens, and limited pedagogical training. Therefore, policy adaptation, teacher training, and strengthening of learning infrastructure are necessary so that PBM can be implemented optimally and sustainably in urban schools.